Structure-Property Relationships in Arapaima Gigas Scales Revealed by Nanoindentation Tests - Torres, FG (2014)
The authors would like to thank the Vicerectorate of Research (VRI) of the Pontificia Universidad Catolica del Peru (PUCP) and the "Consejo Nacional de Ciencia Tecnologia e Innovacion Tecnologica (CONCYTEC)" for financial support.